PINK1 activation–turning on a promiscuous kinase. (7th April 2015) - Aerts, Liesbeth; De Strooper, Bart; Morais, Vanessa A.
Abstract : PINK1 [phosphatase and tensin homologue (PTEN)-induced putative kinase 1] is a serine/threonine kinase targeted to mitochondria and implicated in early-onset recessive Parkinson's disease (PD). Through the phosphorylation of its downstream targets, PINK1 regulates multiple mitochondrial processes, including ATP production, stress-response and mitochondrial dynamics and quality control. The orchestration of such a wide array of functions by an individual kinase requires a fine-tuned and versatile regulation of its activity. PINK1 proteolytic processing, trafficking and localization, as well as different post-translational modifications, affect its activity and function. Unravelling the regulatory mechanisms of PINK1 is essential for a full comprehension of its kinase function in health and disease.